Jakab Reisen utazási iroda csomagajánlatai - Kozár Bettina (2020)
The aim of my thesis is to present the traditional travel agencies and the online booking sites, based on secondary research, what processes are used to organize and book a trip through traditional travel agencies. Along with this, I describe the pros and cons of asking for expert help through an office. With the spread of the internet, the demand for online booking sites is growing rapidly, which could lead to the closure of travel agencies. In my research, I gather the most popular websites today and at the same time I present the risks and benefits of using them. With the information gained during my internship at Jakab Reisen Travel Agency, I present the travel agency, its services and package offers, at the same time, I provide a brief overview of the programs offered by the office. Complementing with my own experience, I describe the target groups and communication activities of the office. Using primary research in my thesis, I survey travelers' opinions about travel agencies and online booking sites, their risks, and what is the most influential factor when people choose travel agencies to organize their trip. Furthermore segmenting the office’s target groups by age and territorial division. Summarizing my surveys, I close my thesis with suggestions.With the summarization and recommendation of the innovations needed to reach the target group.